Severe hemorrhage post robotic-assisted Aquablation: A case report - Dolev Perez; Avital Zeldin; Adam Farkas; Boris Chertin (Urology Case Reports)
Hemorrhage is a potential complication of Aquablation for benign prostatic hyperplasia (BPH). Severe bleeding may require intervention beyond conventional hemostatic measures.We report an 84-year-old male who developed massive hematuria post-Aquablation, leading to hemodynamic instability. Initial conservative measures failed, and angiography identified arterial extravasation. Due to recurrent bleeding, superselective transarterial embolization was performed twice, achieving hemostasis. The patient stabilized and was discharged on postoperative day 12 with improved urinary function.Transarterial embolization is an effective treatment for severe hemorrhage following Aquablation when standard hemostatic techniques fail.